A Gravity Model Approach towards Pakistan's Bilateral Trade with SAARC Countries - Waheed Ullah Jan; Mahmood Shah (Comparative Economic Research. Central and Eastern Europe, 2019)
This research paper attempts to estimate the bilateral trade of Pakistan with SAARC countries using a gravity model of trade. This panel study covers the period from 2003 to 2016. The empirical results are obtained through pooled OLS, fixed-effects, and random-effects estimators. On the basis of Hausman test results, the paper concentrates only on the findings of the fixed-effects model. The empirical findings reveal that the GDPs of both Pakistan and the partner country have a positive impact on bilateral trade. Market size has a negative impact on trade and this is justified on the basis of the absorption effect. Similarly, distance and exchange rate also have a negative correlation with bilateral trade. The study finds that Pakistan has very low trade with India and Afghanistan, despite the common border. A common language has a positive but insignificant impact on Pakistan's bilateral trade. The Paper also attempts to calculate the trade potential of Pakistan. The findings reveal that Pakistan has high trade potential with all SAARC member countries except the Maldives and Afghanistan.
Keywords: F14; F15; F31; F53; 330; bilateral trade; common language; exchange rate; gravity model; population